The natural history of actinic keratosis: a systematic review. (30th August 2013) - Werner, R.N.; Sammain, A.; Erdmann, R.; Hartmann, V.; Stockfleth, E.; Nast, A.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Actinic keratosis (AK) is a common skin lesion with the potential of malignant progression. Progression and regression rates are a matter of debate, and available data have not been summarized systematically. What does this study add? Rates of progression of single AKs into squamous cell carcinoma range between 0% and 0·53% per year, but due to methodological limitations in the identified publications, any estimate of progression rates remains highly uncertain. Rates of regression of single lesions ranged between 15% and 63% per year, with recurrence rates of 15–53%. Spontaneous complete field regression of observed fields on the face and scalp occurred in 0–7·2% of patients.